2009
DOI: 10.1634/stemcells.2008-0319
|View full text |Cite
|
Sign up to set email alerts
|

A Sox1 to Pax6 Switch Drives Neuroectoderm to Radial Glia Progression During Differentiation of Mouse Embryonic Stem Cells

Abstract: The transcription factors Sox1 and Pax6 are expressed sequentially during early mouse embryonic neurogenesis. Sox1 expression starts upon formation of neuroectoderm, whereas Pax6 is subsequently expressed in radial glial cells, the latter giving rise to most neurons of the cerebral cortex. Here we used mouse embryonic stem (ES) cells to study the role of Sox1 and Pax6 in regulating differentiation of neural progenitors. For this purpose, we investigated the effect of overexpression and knockdown of Sox1 and Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
71
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(82 citation statements)
references
References 38 publications
10
71
0
1
Order By: Relevance
“…2). This observation is in line with data by Suter et al 23 showing that PAX6 expression follows the expression of SOX1. The cellular aggregates progressively develop into increasing numbers of neural rosettes.…”
Section: Outline Of Differentiation Protocol and Nomenclaturesupporting
confidence: 93%
“…2). This observation is in line with data by Suter et al 23 showing that PAX6 expression follows the expression of SOX1. The cellular aggregates progressively develop into increasing numbers of neural rosettes.…”
Section: Outline Of Differentiation Protocol and Nomenclaturesupporting
confidence: 93%
“…19 Increase in Pax6 levels, either physiological or ectopic, has been shown to direct cell-cycle exit and differentiation. [19][20][21] Accordingly, we previously observed that ectopic Pax6 expression provoked a postmitotic G 0 /G 1 cell-cycle arrest in HeLa cells. 9 This was however not altered by hRFPL1 RNA interference (data not shown), suggesting that hRFPL1 influence on cell-cycle progression is not sufficient to produce cell-cycle exit and differentiation in Pax6-expressing cells.…”
Section: Discussionmentioning
confidence: 95%
“…However, PAX6-mediated repression of pluripotency genes is not sufficient for induction of NE differentiation; the PAX6A isoform (Table 1) binds to and induces downstream NE layer genes such as Lhx2 (LIM homeobox protein 2), Six3 (sine oculis-related homeobox 3), Fgf8 (fibroblast growth factor 8) and Wnt5b, while a second isoform, PAX6B, potentiates the NE inductive effects of PAX6A through co-repression of pluripotent genes (Zhang et al, 2010). Importantly, these findings are in contrast to those observed during mouse NE specification, where Pax6 is expressed following the formation of NE cells (Bylund et al, 2003) and is linked to the progression of NE cells to radial glia (Suter et al, 2009), suggesting distinct roles for PAX6 in human versus mouse NE specification.…”
Section: Developmental Roles For Pax Genesmentioning
confidence: 90%